2017
DOI: 10.1111/all.13143
|View full text |Cite
|
Sign up to set email alerts
|

The skin barrier function gene SPINK5 is associated with challenge‐proven IgE‐mediated food allergy in infants

Abstract: We report, for the first time, association between SPINK5 variant rs9325071 and challenge-proven IgE-mediated food allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…19 In our study, children born in Asia who subsequently migrated to Australia had a lower risk of food allergy and eczema compared with to differences in allergy rates between growing up in Asia and those growing up in Australia. However, in our previous population-based study in Victoria, we found that parental country of birth was highly correlated (more than 93.0%) with genetically determined Asian or Caucasian ancestry.…”
Section: The Association Between Demographic Factors and Anaphylaximentioning
confidence: 60%
See 1 more Smart Citation
“…19 In our study, children born in Asia who subsequently migrated to Australia had a lower risk of food allergy and eczema compared with to differences in allergy rates between growing up in Asia and those growing up in Australia. However, in our previous population-based study in Victoria, we found that parental country of birth was highly correlated (more than 93.0%) with genetically determined Asian or Caucasian ancestry.…”
Section: The Association Between Demographic Factors and Anaphylaximentioning
confidence: 60%
“…However, in our previous population-based study in Victoria, we found that parental country of birth was highly correlated (more than 93.0%) with genetically determined Asian or Caucasian ancestry. 19 In our study, children born in Asia who subsequently migrated to Australia had a lower risk of food allergy and eczema compared with to differences in allergy rates between growing up in Asia and those growing up in Australia. 24 While both eczema and food allergy were around twice as common in Australian-born Asian children as in non-Asian children, the prevalence of asthma was not similarly increased, suggesting a different pathogenesis between asthma and other allergic diseases.…”
Section: The Association Between Demographic Factors and Anaphylaximentioning
confidence: 60%
“…Included studies were of varying sample sizes with the smallest study having 30 food allergy Caucasian cases and 35 nonallergic Caucasian controls, while the largest study was a GWAS with 2197 European subjects (671 with food allergy, 144 nonallergic nonsensitized controls and 1382 European controls of uncertain phenotype) . The majority (n = 11) of included studies were conducted in only “Caucasian,” “European” or “White” populations, whereas 11 studies were carried out in predominantly Caucasian populations alongside other ethnicities (“Asians,” “Mixed” and “African American”) . Four others were carried out in Japanese populations, one was carried out in a Taiwanese population, and there were five studies where ethnicity was not mentioned …”
Section: Resultsmentioning
confidence: 99%
“…28 Genetic mutations in the SPINK5 gene, which encodes a serine peptidase inhibitor Kazal-type 5 essential for skin regeneration, were challenge-proven to be associated with IgE-mediated food allergy in children. 29 Preliminary results suggest that the polymorphism variant rs9325071 led to increased skin permeability as measured by transepidermal water loss. There is recent evidence suggesting that genetic variants related to adult lung function are associated with lung function and asthma in 10-year-old children.…”
Section: G Ene Ti C S Of Allerg I C D Is E a S E S And A S Thmamentioning
confidence: 96%